SISTEM INFORMASI ONLINE SHOP BERBASIS WEB DENGAN METODE SDLC: WEB-BASED ONLINE SHOP INFORMATION SYSTEM WITH SDLC METHOD - Albertus Laurensius Setyabudhi; Zulfirman Syahputra Hasibuan (YCMM, 2020)
Tassia Store was founded in 2015, where initially it started as just setting up a shop and has now switched to an online shop. Tassia Store is an olshop that sells bags, clothes, and shoes. the products that are sold are more well-known products such as prada, nike, addidas etc. Tassia Store also sells watches, belts, and bags with various motifs for teens and adults. With the increasing number of fans on the Tassia Store. It is undeniable that fans of branded products have become a necessity today, especially for teenagers, then Tassia Store wants to develop its business by having a Web-based online sales information system. Tassia Store currently does not have its own website to market the products it sells. In addition, orders are still made by recording manually so it is inconvenient if a customer cancels their order. Currently, Tassia Store markets its products through resellers and online using the Instagram application media which is still an obstacle because the menu display regarding the product is not fully available, such as existing stock, ordering, promotion, and payment methods. Another obstacle is also a problem because not all customers use the Instagram application media so that the products we have promoted through the application media cannot be reached by all customers. Therefore, the Tassia Store still needs an expansion in the business of selling its goods so that it is easy for customers to order and find out information about the goods in the Tassia Store.